2018
DOI: 10.3390/ijerph15071486
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis Severity—A Risk Factor of Insulin Resistance Independent of Metabolic Syndrome

Abstract: Background: It is still debatable whether psoriasis increases cardiovascular risk indirectly since it is associated with metabolic syndrome or is an independent cardiovascular risk factor. The aim of this study was to evaluate psoriasis severity as an independent predictor of insulin resistance (IR) irrespective of the presence of metabolic syndrome (MetS). Methods: This was a case control study including 128 patients stratified into two groups: patients with psoriasis and metabolic syndrome vs. patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
3
31
1
1
Order By: Relevance
“…Despite this finding, Lee et al26 described that, in addition to an overall increased risk of T2D in PsO patients, the risk is modulated by both PsO severity, comorbidities and concomitant medication in a large Taiwan cohort. Also, while overt T2D is seemingly not related to severity of PsO, intermediate phenotypes underlying the risk of T2D such as insulin resistance, fasting blood glucose and hemoglobin A1C may still be associated with the severity of PsO 27. Naldi et al28 concluded that the association found between PsO and T2D in other studies might have been confounded by lifestyle, smoking, overweight, or long disease duration, somewhat disagreeing with Lee et al26 However, Mahé et al29 showed that patients with adult onset PsO had significantly more comorbidities compared to childhood onset patients.…”
Section: Introductionmentioning
confidence: 98%
“…Despite this finding, Lee et al26 described that, in addition to an overall increased risk of T2D in PsO patients, the risk is modulated by both PsO severity, comorbidities and concomitant medication in a large Taiwan cohort. Also, while overt T2D is seemingly not related to severity of PsO, intermediate phenotypes underlying the risk of T2D such as insulin resistance, fasting blood glucose and hemoglobin A1C may still be associated with the severity of PsO 27. Naldi et al28 concluded that the association found between PsO and T2D in other studies might have been confounded by lifestyle, smoking, overweight, or long disease duration, somewhat disagreeing with Lee et al26 However, Mahé et al29 showed that patients with adult onset PsO had significantly more comorbidities compared to childhood onset patients.…”
Section: Introductionmentioning
confidence: 98%
“…A diet high in sugar‐sweetened drinks and low in fruits and vegetables is associated with a pro‐inflammatory adipokine profile with increased plasma levels of TNF‐α, leptin and monocyte chemotactic protein 1 in Mexican‐Americans . Psoriasis severity is an independent risk factor of the Homeostasis Model of Assessment – Insulin Resistance, and is also correlated with the levels of pro‐inflammatory adipokines like leptin . Taken together, the high intake of confection may lead to the exacerbation of psoriatic symptoms and the promotion of insulin resistance: the high intake of confection may promote the secretion from adipose tissues of pro‐inflammatory adipokines like TNF‐α or resistin, which may act on dendritic cells, T cells or keratinocytes, and aggravate the inflammation in the skin .…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary, environmental, and immunologic elements seem to assume an essential job in the advancement, seriousness, and PS's relationship with metabolic syndrome (MS) [3]. MS is defined by multiple components (high blood pressure, abdominal obesity, glucose intolerance, and dyslipidemia) of risk factors that arise primarily from insulin resistance mostly mediated by 1 2 3 4 1 inflammatory cytokines, such as tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6) together with leptin and adiponectin, which are molecules also found in PS [4]. MS by itself could cause an increased risk for cardiovascular diseases (CVD) and premature mortality.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports also suggest that PS is a significant independent risk factor for cardiometabolic diseases and insulin resistance, regardless of BMI. Also, a systemic inflammatory state known as the "psoriatic march" is believed to be the cause behind the interplay of inflammatory mediators, such as cytokines and adipokines, that lead to insulin resistance, atherosclerosis, and cardiovascular diseases (CVD), such as acute coronary syndromes and cerebral infarction [4,5]. Factors related to cardiovascular events, such as smoking, alcohol, and physical inactivity, are also prevalent among psoriatic patients.…”
Section: Introductionmentioning
confidence: 99%